The Problem of Justifying Inductive Reasoning - Nedeljković, Mitar Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
In this paper, the author considers the classical strategies of defense from Hume’s argument against induction, and assesses the extent to which they were found to be successful. Synthetic, linguistic, a priori, pragmatic, and inductive strategies of defending induction are considered, as well as the question of the extent to which the justification of induction is a problem for grounding scientific knowledge. A new argument is introduced for the a priori justification of induction, as well as a critique of the synthetic and inductive defenses of induction by Black and Jacquette.